SYSTEMATIC LITERATURE REVIEW: USING ENGLISH MOVIES TO DEVELOP ESL LEARNERSâ€™ SPEAKING CONFIDENCE - Nurul Hidayah Awang Asim; Wardatul Akmam Din; Kamsilawati Kamlun; Suyansah Swanto, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Can English movies improve ESL learnersâ€™ speaking confidence? What are the suggested ways to implement English movies in acquiring speaking confidence for ESL learners? The main goal of the review is to study how English movies can aid ESL learners in higher education who struggle with speaking confidence. The search phrases used in these databases were â€œEnglish moviesâ€ AND â€œconfidenceâ€ and â€œEnglish moviesâ€ AND â€œspeakingâ€ in order to acquire a list of relevant research. The first aspect that we will discuss in this review is the issue of low speaking confidence that is usually caused by language anxiety, lack of self-esteem and fear of judgement among other reasons. The articles collected represent language learners from different age ranges such as young kindergarten learners until university level learners. In addition to that, we will also investigate further into the research from the databases available for English movies that can be utilized as instructional aid for ESL learners to acquire speaking confidence. To find relevant research publications, four databases were used: ProQuest, Science Direct, Scopus and JSTOR. The review was carried out by using the UMS Library's access to subscribed databases. As part of this systematic review, we devised a search strategy to collect relevant literature. Researchers over the years have differing opinions on the current situation. The majority of the study indicates that language learners often struggled from speaking anxiety and fear of public speaking whether it is due to judgement of others or their own limited speaking abilities. We have mapped the literature to enable readers to understand the lessons from past literature that can be learned as well as provide a future agenda to the issue.